Neurodiversity and Thriving: A Case Study in Theology-Informed Psychology - Leidenhag, Joanna (Studies in Christian ethics, 2023)
The concept of ‘neurodiversity’ to speak of conditions such as autism, dyslexia, and others as differences, not disorders or pathologies, relies on a robust account of human flourishing that can incorporate these conditions. Conceptions of illness and well-being are always partially theological, whilst also having to be grounded in the empirical realities of the present time. Therefore, positive developmental psychology is a particularly apt field for developing a theology-informed psychology. This article argues that recent work in theology-engaged psychology of thriving, as opposed to subjective flourishing, is the best approach to securing a vision of well-being for neurodiverse persons.